3y+2(3)=-5

Simple and best practice solution for 3y+2(3)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+2(3)=-5 equation:


Simplifying
3y + 2(3) = -5

Multiply 2 * 3
3y + 6 = -5

Reorder the terms:
6 + 3y = -5

Solving
6 + 3y = -5

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3y = -5 + -6

Combine like terms: 6 + -6 = 0
0 + 3y = -5 + -6
3y = -5 + -6

Combine like terms: -5 + -6 = -11
3y = -11

Divide each side by '3'.
y = -3.666666667

Simplifying
y = -3.666666667

See similar equations:

| 2(2x+96)=2(3x+80) | | 30-3c=9 | | 7x^2-4=48 | | 4x-17x^1/2+15=0 | | 4f+12=2f+24 | | 15t-9-8t=5 | | x+.40=168 | | 5/6h-3/4h=-13/6+2/12 | | 0.4x-0.3(30+x)=-0.2(30) | | -2(4x+9)=-8x-18 | | 8.77xy=8.00 | | x+7x-8=8 | | (3x-9)(x+4)=0 | | 4y+228=52 | | 12a-24=12 | | 3x+4(x+3)=68 | | 3x-8+x+12=17 | | -15*5/3c*8 | | -5(2x-1)=3(x+5) | | 56y+1=781 | | 6x+8=290 | | -3+1=x+9-4x | | v/4-10=5 | | 1.5x-18=0.5x | | 22/11x9-3 | | -4/3+x2+1/3x-8+8/3x | | 5v^2=20 | | 2/63/6= | | (2r-4s+6t)(2r-4s+6t)= | | 5y+y-9=8y+1 | | 4+12/4-2 | | 80x^2=50 |

Equations solver categories